An odyssey of suturing cardiac wounds: Lessons from the past. Issue 7 (2nd June 2020) - Flécher, Erwan; Leguerrier, Alain; Nesseler, Nicolas
Abstract: Background and aim of the study: Cardiac wounds have been described for centuries and still remain to be fatal. For a long period of time, the suturing of a myocardial laceration was thought to be absolutely impossible if not sacrilege. Methods: It is only at the end of the 19th century that pioneers decided to defy such a dogma in desperate cases. Results: Nowadays, it seems obvious that a cardiac stab wound requires emergent surgery whenever possible. Conclusions: The story of cardiac wounds highlights nicely the change of mind that is required to accept progress and new procedures in medicine.